CASE STUDY: PHYSIOTHERAPY PROGRAM IN BELL'S PALSY - Endrawati, Ika; Rahman, Farid; Riza, Oni Iftaru; Rochmawati, Rizki Wahyu Dhani (Academic Physiotherapy Conference Proceeding, 2021)
Introduction:Bell's palsy is an acute facial nerve disease where the first symptom is pain in the mastoid area and causes facial paralysis1. In one year the incidence of this disorder can occur in 23 people out of 100,000 people2. Problems caused by Bell's palsy include the occurrence of facial asymmetry, a decrease in muscle strength on the side of the injured face, which results in decreased functional ability and interferes with activities. Bell's palsy treatment can be given medical therapy and physiotherapy programs. Physiotherapy plays a role in increasing muscle flexibility, facilitating weak muscles in carrying out movements to improve muscle work. This report follows up on the research of3, conducted the same program on 8 patients with similar complaints, getting results that are in accordance with this study. Case Presentation: A 50 years male, had a profession as civil servants and muslim, residing in Ngawi, East Java. The examination that has been carried out on the patient found that there is asymmetry on one side of the face, there are limitation in the movement of opening and closing the eyes, limitations in smiling, puffing the cheeks and smile, while the movements of frowning and raising the eyebrows have not been able to do. Management and Outcome:Physiotherapy modalities with infrared, electrical stimulation, massage facial to increasing muscle flexibility, facilitating weak muscles in carrying out movements to improve muscle work. Furthermore, to determine the patient's progress, measurement results were used in the form of a Manual Muscle Testing (MMT) to determine the increase in strength in facial muscle and Ugo Fisch Scale to determine the increase in functional ability in facial muscle. Discussion: This study was to measure the effects of electrical stimulation, infrared and facial massage on patients with Bell's palsy. This report will follow up the research of3 about their study on 8 patient with the same complaint whether there are result that are ini sync with this study. Conclusion: It is proven that cases of Bell’s Palsy that receive in the form of infrared, electrical stimulation and massage can increase muscle strength and can increase facial functional activity.